Revisión de modelos de gestión ambiental en instituciones de educación superior - Monroy-Abril, Pilly Constanza; Castrillón-Cardona, William Fernando; Daza-Ardila, Diana del Socorro (Revista Científica, 2016)
Higher Education Institutions (IES) have increased in recent decades concern and interest in improving institutional environmental management and achieve high levels of sustainability; to this end, have retaken management models created for the industry, which have been tailored to the needs of higher education institutions, giving effect to the consolidation of specific models, promoting actions on missionary commitments of universities, such as: training , research, extension and service provision. literature review was conducted to describe, first environmental management models currently being developed in the IES; and the challenges to be overcome educational institutions and opportunities for achieving environmental sustainability in universities worldwide.